Undiscovered Potential: Ge Catalysts for Lactide Polymerization. Issue 1 (15th November 2019) - Rittinghaus, Ruth D.; Tremmel, Jakub; Růžička, Ales; Conrads, Christian; Albrecht, Pascal; Hoffmann, Alexander; Ksiazkiewicz, Agnieszka N.; Pich, Andrij; Jambor, Roman; Herres‐Pawlis, Sonja
Abstract: Polylactide (PLA) is a high potential bioplastic that can replace oil‐based plastics in a number of applications. To date, in spite of its known toxicity, a tin catalyst is used on industrial scale which should be replaced by a benign catalyst in the long run. Germanium is known to be unharmful while having similar properties as tin. Only few germylene catalysts are known so far and none has shown the potential for industrial application. We herein present Ge complexes in combination with zinc and copper, which show amazingly high polymerization activities for lactide in bulk at 150 °C. By systematical variation of the complex structure, proven by single‐crystal XRD and DFT calculations, structure–property relationships are found regarding the polymerization activity. Even in the presence of zinc and copper, germanium acts as the active site for polymerizing probably through the coordination–insertion mechanism to high molar mass polymers. Abstract : On the route towards a benign production of PLA, we came across Germanium. With its similar properties to tin due to its close position in the periodic table, germanium, being completely nontoxic, is a promising, but so far rather neglected candidate for an alternative catalyst for industrial lactide polymerization. With high molar masses after 1 h of polymerization at 150 °C in bulk, these examples show the high efficiency germanium catalysts can reach (see scheme).